+0  
 
0
48
1
avatar+634 

Please help:

AdamTaurus  Oct 23, 2017

Best Answer 

 #1
avatar+5261 
+1

When a quadratic equation is in the form  f(x)  =  a(x - h)2 + k ,  the vertex is  (h, k)

 

For this problem, they tell us the vertex is  (-1, 5) , so we know that

 

f(x)  =  a(x - -1)2 + 5

 

f(x)  =  a(x + 1)2 + 5

 

We know it goes through the point  (2, -13) , which means  f(2) = -13

 

f(2)  =  a(2 + 1)2 + 5       And  f(2) = -13

 

-13  =  a(2 + 1)2 + 5

 

-13  =  9a + 5

 

-18  =  9a

 

-2  =  a

 

Now we've found  a  , so we know that

 

f(x)  =  -2(x + 1)2 + 5            And here's a graph to check it.

hectictar  Oct 23, 2017
Sort: 

1+0 Answers

 #1
avatar+5261 
+1
Best Answer

When a quadratic equation is in the form  f(x)  =  a(x - h)2 + k ,  the vertex is  (h, k)

 

For this problem, they tell us the vertex is  (-1, 5) , so we know that

 

f(x)  =  a(x - -1)2 + 5

 

f(x)  =  a(x + 1)2 + 5

 

We know it goes through the point  (2, -13) , which means  f(2) = -13

 

f(2)  =  a(2 + 1)2 + 5       And  f(2) = -13

 

-13  =  a(2 + 1)2 + 5

 

-13  =  9a + 5

 

-18  =  9a

 

-2  =  a

 

Now we've found  a  , so we know that

 

f(x)  =  -2(x + 1)2 + 5            And here's a graph to check it.

hectictar  Oct 23, 2017

11 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details